2013
DOI: 10.5897/ajpp2013.3821
|View full text |Cite
|
Sign up to set email alerts
|

Survey based study on the use of non-prescription drugs among pharmacists and non-pharmacists

Abstract: The aim of this study was to determine the attitude of pharmacists and non-pharmacists in Karachi towards the use of non-prescription medicines. A cross-sectional survey was conducted from August 2012 to October 2012 among pharmacist and non-pharmacists. Data was analyzed and results were compared using Chi-square test with the help of statistical software package (SPSS version 19). Overall prevalence of self-medication was found to be 81.28%. Factors like busy life schedule (27.58%), previous experience of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…The finding of this study suggested that two-thirds (67.5%) of health professionals were self-medicating with modern medicines. This figure was comparable with findings reported from study conducted in Malaysia [ 13 ]; and it was less than the findings reported from study conducted in India, Pakistan and Ghana [ 10 , 12 , 14 ]; and it was higher than the reports from study done in America [ 16 ]. This discrepancy might be due to different factors such as variation in income of the professionals, availability of social health insurance for professionals, and governing laws, which prohibit sales of prescription only medicines as over the counter.…”
Section: Main Textsupporting
confidence: 86%
See 1 more Smart Citation
“…The finding of this study suggested that two-thirds (67.5%) of health professionals were self-medicating with modern medicines. This figure was comparable with findings reported from study conducted in Malaysia [ 13 ]; and it was less than the findings reported from study conducted in India, Pakistan and Ghana [ 10 , 12 , 14 ]; and it was higher than the reports from study done in America [ 16 ]. This discrepancy might be due to different factors such as variation in income of the professionals, availability of social health insurance for professionals, and governing laws, which prohibit sales of prescription only medicines as over the counter.…”
Section: Main Textsupporting
confidence: 86%
“…A study conducted in India showed that a lower degree of illness is the main reason of practicing self-medication among health professionals [ 12 ] while studies done in Malaysia and Pakistan showed familiarity with treatment as a main reason of practicing self-medication [ 7 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common reasons for self-medication were prior experience of the disease or similar symptoms (Al-Azzam et al 2007;James et al 2008;Yousef et al 2008;Zafar et al 2008;Scicluna et al 2009;Mumtaz et al 2011;Jalilian et al 2013), certainty of its safety, (Jalilian et al 2013), prior consumption of the drug (Jalilian et al 2013), busy offices of physicians (Jalilian et al 2013;Shoaib et al 2013), and nonseriousness of the illness (James et al 2008;Yousef et al 2008;Mumtaz et al 2011;Jalilian et al 2013;Shoaib et al 2013) or low severity of disease (Ullah et al 2013). Long waiting time to be seen by doctors (James et al 2008;Yousef et al 2008) and avoiding the cost of doctors' visits were also reported as common reasons for self-medication (Yousef et al 2008).…”
Section: Sources and Reasons For Self-medicationmentioning
confidence: 99%
“…Past studies revealed that the prevalence of self-medication among university students was (43.2%) in Ethiopia 10 This practice is influenced by many factors, such as education, family, society, law, availability of drugs and exposure to advertisements 9 . A high level of education and professional status has been mentioned as predictive factors for self-medication 17,18,19 . The reasons for self-medication mentioned in the literature are mild illness, previous experience of treating similar illness, economic considerations 10,11,12,13,14,15 .…”
mentioning
confidence: 99%
“…Looking at this practice among medical undergraduates is also very vital as they represent the future generation of drug prescribers and health team worker 16,17,18 .…”
mentioning
confidence: 99%